PENGARUH TARIF PAJAK, KEBIJAKAN DIVIDEN, RISIKO BISNIS TERHADAP HARGA SAHAM: Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia - Eka Siti Rahayu; Wiwit Irawati (Gapenas Publisher, 2022)
The share price is the price of a share that occurs on the stock market at a certain time determined by market participants and is determined by the demand and supply of the shares concerned in the capital market. Increases and decreases in stock prices are influenced by many factors. This study aims to determine the effect of Tax Rates, Dividend Policy and Business Risk on Stock Prices in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020. The sample selection method used purposive sampling method, based on this method obtained 10 companies with a research year of 5 years, the total research data obtained were 50 observational data. The analysis technique used is panel data regression which is a combination of time series data and cross section data. The test results show that partially the tax rate has no effect on stock prices. Dividend policy and business risk have a significant effect on stock prices. Simultaneously shows that Tax Rates, Dividend Policy and Business Risk simultaneously affect stock prices in consumer goods industrial sector companies listed on the Indonesia Stock Exchange in 2016-2020